Female genital mutilation and cutting: a survey of child abuse pediatricians - Grace Pipes; Spencer Dunleavy; Jocelyn Brown (BMC, 2024)
Abstract Background As global immigration from countries with a high prevalence of female genital mutilation and cutting (FGM/C) has grown in the United States (US), there is need for pediatricians to have adequate training to care for these patients. The objective of this study is to determine the level of knowledge and attitudes of child abuse pediatricians (CAPs) towards FGM/C in the US. Methods This cross-sectional study distributed a peer-reviewed survey to US CAPs-members of the Helfer Society-to assess their attitudes, knowledge, clinical practice, and education about FGM/C. Data was analyzed using descriptive statistics, Kruskal-Wallis tests, and Fisher's exact test. Results Most of the 65 respondents were aware that FGM/C is illegal (92%) and agreed that it violated human rights (99%). Individuals reporting previous training related to FGM/C were significantly more likely to correctly identify World Health Organization types of FGM/C (p < 0.05) and report confidence in doing so (p < 0.05). Only 21% of respondents felt comfortable discussing FGM/C with parents from countries with a high prevalence of FGM/C. Sixty-three percent were not aware of the federal law, and 74% were not aware of their own state's laws about FGM/C. Conclusions US CAPs have high rates of training related to FGM/C; however, they need additional training to increase confidence and ability to identify FGM/C. FGM/C remains a topic that CAPs find difficult to discuss with families. With culturally sensitive training, CAPs have the opportunity to help manage and prevent the practice by serving as educators and experts for general pediatricians.